A Weak Acidic and Strong Coordinated Deep Eutectic Solvent for Recycling of Cathode from Spent Lithium‐Ion Batteries. Issue 16 (1st July 2022) - Tian, Yurun; Chen, Wenjun; Zhang, Baolong; Chen, Yu; Shi, Ruifen; Liu, Shuzi; Zhang, Zhenchuan; Mu, Tiancheng
Abstract: The leaching and recycling of valuable metals via environmentally benign solvents is important because of the ever‐increasing waste lithium‐ion batteries, but it remains a challenge. Herein, a multi‐functional deep eutectic solvent (DES) based on lactic acid (LA) and guanidine hydrochloride (GHC) was used to extract cobalt and lithium ions from LiCoO2 . Due to the strong acidity (protons) and abundant chlorine coordinating ions of LA/GHC, the solubility of LiCoO2 in LA/GHC could reach as high as 19.9 mg g −1 (stirred at 80 °C for 24 h), and a little LiCoO2 powder even could be dissolved at room temperature without stirring. Oxalic acid was used to strip and separate the oxalates of cobalt and lithium. Furthermore, LA/GHC could be recycled with a similar dissolving performance. This work avoided using corrosive acids and could be realized at low temperature (80 °C), making it energy‐saving and cost‐effective. It shows DESs have great potential in extracting strategically important metals from LiCoO2 cathodes and provides an efficient and green alternative for sustainable recycling of spent lithium‐ion batteries. Abstract : Battery recycling : A deep eutectic solvent based on lactic acid and guanidine hydrochloride is proposed for the extraction of cobalt and lithium from lithium‐ion battery cathodes, and high solubility is achieved at low temperatures. The process avoids the use of toxic reagents and is more efficient and environmentally benign.